Recent advances in Bio-mass by electrochemically strategies generated hydrogen gas production: Environmentally sustainable technologies innovation - Mugheri, Abdul Qayoom; Khan, Shaista; Asghar sangah, Ali; Bhutto, Aijaz Ahmed; Laghari, Muhammad Younis; Mugheri, Nadeem Ahmed; Jamali, Asif Ali; Mugheri, Arsalan Ahmed; Sodho, Nagji; Mastoi, Abdul Waheed; Kandhro, Aftab (Elsevier, 2024)
The potential of green hydrogen as in transitioning to a free pollution energy infrastructure. Green hydrogen gas is produced using renewable energy sources, typically through the process of electrolysis, and is considered environment friendly because it does not emit carbon dioxide when produced. While solar water redox reaction using photochemical and electrochemical methods is an elegant way to harvest green hydrogen production, it can be challenging to make this process economically competitive, especially for low-cost products like hydrogen. To address this challenge, the proposes a solution, which is to produce hydrogen during the photoelectrochemical process. In this demonstration of the (photo)electrochemically generated hydrogen (H2) for the homogeneous and hydrogenation. The coupled process offers greater stability compared to direct electrochemical hydrogenation and it provides more flexibility in controlling the chemical reactions involved. Overpotential refers to the extra energy required to drive a reaction and coupling the processes can help minimize this overpotential. An overall ∼58 conversion of the produced hydrogen is confirmed for this process, indicating the efficiency of the approach. Additionally, a techno-economic assessment of the proa strategy to make green hydrogen production economically competitive by co-producing value-added chemicals, using ascorbic acid. This approach enhances the economic feasibility of green hydrogen production but also adds value to the process by producing valuable chemical products. © 2023 Elsevier Ltd